The Correlation of Pain Intensity and Sleep Quality in the Elderly - Juwariah, Titik; Priyanto, Agus; Pratidina, Angga (Health Gate, 2024)
AbstractIncreasing age causes the elderly to experience biological, physical, psychological and social changes, these changes affect all aspects of life, including their health, one of which is pain. Previous research has shown that as many as 50% of elderly living in the community and 45% - 80% of those living in nursing homes suffer from this problem. Pain impacts the quality of sleep. Sleep quality affects physical and psychological aspects, namely fatigue, anxiety, irritability, disturbed concentration, stress which can increase the risk of suicide. The purpose of this study was to determine the relationship between pain intensity and quality of sleep for the elderly at Tresna Wherda Social Institution Tulungagung. The research design used in this study was a correlation study with a cross sectional approach. The population in this study were all elderly people at PSTW Tulungagung in January 2023, namely 80 people. The sample size is determined by the Lameshow formula, as many as 66 people. The sampling technique in this study was by means of purposive sampling. Data collection on pain intensity used the Visual Analog Scale (VAS) questionnaire, and sleep quality used the Pittsburgh Sleep Quality Index (PSQI). Data analysis using Spearman Rank. The results showed that most of the elderly had mild pain intensity (51.5%), the quality of sleep for the elderly was mostly good (80.3%), and there was a relationship between pain intensity and quality of sleep in the elderly at PSTW Tulungagung with p-value = 0.012 with a correlation coefficient = 0.309 (medium). It is hoped that the results of this research can become a source and knowledge that can add insight in dealing with elderly people with pain and sleep disorders who are in the information community and special groups.Keywords: pain intensity; sleep quality; elderly